Pemanfaatan E-journal yang Dilanggan Perpustakaan Fakultas Kedokteran Universitas Andalas Bagi Mahasiswa Kedokteran - Rejeki, Ovie Dwi; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purpose of this research were to the use of e-journals subscribed library Andalas University School of Medicine for medical students. Data were collected through direct observation and questionnaires. By analyzing the data, it was concluded the following. First, medical school students to access e-journal as a learning facilities provided by the library. Second, the benefits of e-journal is not only limited reference to the percentage of lectures and student assignments. E-journal information as well as research materials, consideration concoction of drugs, consideration of disease prevention, disease diagnosis consideration. Third, students access the e-journal is not always rely library service hours and a certain place, but can be anywhere and anytime who have the facilities to connect to access e-journal. Fourth, the sources of e-journals accessible to students depending on the level of information needs, the most important is the medical database or website that references a source-to-date information. More and more in knowledge and research, the more in the need of information you want extracted and obtained for students. Keywords: e-journal; library; medical students